On Adverbial Ante-Position and Operator Scope in Coptic - Uljas, Sami (Zeitschrift für ägyptische Sprache und Altertumskunde, 2012)
It is argued that in Coptic ante-position of adverbial expressions may be motivated by a desire to delimit and indicate the precise scope of negative, modal, conditional and information-structuring operators. Two principal strategies are distinguished. The ante-position may serve to exclude an adverbial expression from falling within the scope of e.g. a negation. Conversely, a similar positioning of an adverbial may have the function of including it within the scope of an (initial) operator.